2006
DOI: 10.1007/s10236-005-0053-y
|View full text |Cite
|
Sign up to set email alerts
|

Properties of suspended sediment in the estuarine turbidity maximum of the highly turbid Humber Estuary system, UK

Abstract: Measurements are presented of the properties of suspended particulate matter (SPM) in the estuarine turbidity maximum (ETM) of the upper Humber and Ouse estuaries during transient, relatively low freshwater inflow conditions of September 1995. Very high concentrations of near-bed SPM (more than 100 g l −1 ) were observed in the low-salinity (less than 1), upper reaches. SPM within the ETM consisted largely of fine sediment (silt and clay) that existed as microfloc and macrofloc aggregates and individual partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…grain-size, helped consolidating mass inventories. Likewise, origin and fate of matter in estuarine turbidity maximum zones can be better identified by measuring the quality of TSM, as done for example in the Humber-Ouse estuary (Uncles et al, 2006) or Elbe estuary (Van Beusekom and Brockmann, 1998). The portion of particulate organic matter (POM) of TSM is of particular interest, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…grain-size, helped consolidating mass inventories. Likewise, origin and fate of matter in estuarine turbidity maximum zones can be better identified by measuring the quality of TSM, as done for example in the Humber-Ouse estuary (Uncles et al, 2006) or Elbe estuary (Van Beusekom and Brockmann, 1998). The portion of particulate organic matter (POM) of TSM is of particular interest, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The classification and terminology of the constituent layers vary in the literature. The upper layer in the three-layer models is often termed low to highly concentrated suspension (Winterwerp and van Kesteren, 2004) or mobile suspension (Ross, Lin, and Mehta, 1987;Ross and Mehta, 1989;Uncles, Stephens, and Harris, 2006). In this fluid-supported layer, particles settle freely in SSCs of a few milligrams to grams per liter (Ross, Lin, and Mehta, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Additional complications arise from the effects of sediment composition on flocculation processes. In many coastal environments, clay and silt sediments are often dominant (Carniello et al, 2012;Hill et al, 2013;Safak et al, 2013;Uncles et al, 2006). Previous studies have mostly focused on mud-sand mixtures (Amy et al, 2006;Cuthbertson et al, 2018;Le Hir et al, 2011), and the results have indicated that different compositions of sediments will influence the average floc size and floc formation rates (Cuthbertson et al, 2010(Cuthbertson et al, , 2018.…”
mentioning
confidence: 99%